Physician Fees and Managed Care Plans - Jack Zwanziger (SAGE Publishing, 2002)
One of the objectives of managed care organizations (MCOs) has been to reduce the rate of growth of health care expenditures, including that of physician fees. Yet, due to a lack of data, no one has been able to determine whether MCOs have been successful in encouraging the growth of price competition in the market for physician services in order to slow the growth in physician fees. This study uses a unique, national-level data set to determine what factors influenced the physician fees that MCOs negotiated during the 1990-92 period. The most influential characteristics were physician supply and managed care penetration, which suggest that the introduction of competition into the health care market was an effective force in reducing physician fees.